Role of Genetics, Genomics, and Breeding Approaches to Combat Stripe Rust of Wheat - Jamil, Shakra; Shahzad, Rahil; Ahmad, Shakeel; Fatima, Rida; Zahid, Rameesha; Anwar, Madiha; Iqbal, Muhammad Zaffar; Wang, Xiukang (Frontiers in Nutrition, 2020)
Puccinia striiformis (Pst) is a devastating biotrophic fungal pathogen that causes wheat stripe rust. It usually loves cool and moist places, and can cause 100% crop yield losses in a single field when triangle for disease establishment is present. Billions of dollars are lost due to fungicide’s application to reduce stripe rust damage worldwide. Pst is a macrocyclic, heteroecious fungus that require primary (wheat or grasses) as well as secondary host (Berberis or Mahonia spp.) for completion of life cycle. In this review, we have summarized the knowledge about pathogen life cycle, genes responsible for stripe rust resistance and susceptibility in wheat. At the end we discussed the importance of conventional and modern breeding tools for development of Pst resistance wheat varieties. According to our knowledge genetic engineering and genome editing are less explored tools for development of Pst resistant wheat varieties hence we highlighted the putative use of advanced genome modifying tools i.e. base editing and prime editing for development of Pst resistance wheat